The cariogenic effect of school snack on risk levels with caries assessment tool study in children age 12-15 years old - Yulita Subandari; Bambang Priyono; Al Supartinah (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
The teen years, around the age of 12-14 years, is the time for children to experience physical growth spurt, which increases their appetite, so they love snacks and develop snack eating habit at school. This study aims to determine the cariogenic effect of school snacks on caries risk based on the caries assessment tool (CAT) study in children aged 12-15 years. This is an observational quantitative study with cross-sectional research design. The population in this study were all students of class VII, aged 12-15 years in SMP Negeri (SMPN) Kulon Progo, comprised of 2,047 students. This study used a cluster proportional random sampling technique and obtained a sample size of 100 respondents. Data were collected using a questionnaire about school snacks and observation of caries risk assessment was based on CAT, and the data were analyzed using the Chi-Square test. The results showed that the cariogenic school snacks consumed by children aged 12-15 years in SMPN Kulon Progo were in the low category (71%); risk of caries occurrence based on CAT studies in children aged 12-15 years was in the high category of 50%. There was no significant effect on cariogenic school snacks on the level of caries risk based on CAT study in children aged 12-15 years.